The Role of Ideological Beliefs and Tolerance for Uncertainty in Seeking Esoteric Services - Antonova, N.A.; Eritsyan, K.Y.; Usacheva, N.M. (Socialʹnaâ Psihologiâ i Obŝestvo, 2023)
Objective. Assessing the relationship between the use of esoteric services, tolerance for uncertainty and beliefs unpredictability and determinism. Background. Esoteric practices today represent a significant market sector worldwide and in Russia. At the same time, predictors of use of such services are still poorly studied. Most psychological research has focused on beliefs in the paranormal or supernatural, while much less attention has been paid to associated behavioral practices. Study design. Cross-sectional survey study.Participants. Adult population of Russia (N = 1498, 47% males). A quota sample of an online panel was used to represent the adult population of Russia in terms of gender and age composition and representation of the urban and rural population. Mean age 41,6 years old (SD = 12,72). Measurements. Russian-language versions of tolerance to uncertainty (MSTAT-I) and belief in freedom/determinism (FAD-Plus) scales, assessment of socio-demographic and behavioral parameters using survey methods. Results. Seeking esoteric services is associated with a range of beliefs about determinism and unpredictability and is more common among women and people with high religiosity. Contrary to the hypothesis put forward, no relationship was found between seeking esoteric services and tolerance of uncertainty. Conclusions. Seeking esoteric services is closely related to beliefs about the world: belief in determinism (both fatalistic and scientific) may be a facilitator of the use of such services, while beliefs in unpredictability and freedom are negatively associated with the use of such services. Цель. Оценка взаимосвязи использования эзотерических услуг, толерантности к неопределенности и мировоззренческих убеждений о случайности и детерминированности. Контекст и актуальность. Эзотерические практики представляют сегодня значительный сектор услуг, на который есть спрос в России и мире. При этом предикторы обращения к ним до сих пор слабо изучены. В основном психологические исследования сконцентрированы на изучении веры в паранормальное или сверхъестественное, тогда как сопутствующим поведенческим практикам уделяется существенно меньше внимания. Дизайн исследования. Кросс-секционное опросное исследование. Участники. Взрослое население России (N = 1498, мужской пол - 47%). Использована квотная выборка онлайн-панели, позволяющая репрезентировать взрослое население России в контексте половозрастного состава и репрезентации городского и сельского населения. Средний возраст составил 41,6 лет (SD = 12,72). Методы (инструменты). Русскоязычные версии шкал толерантности к неопределенности (MSTAT-I) и веры в свободу/детерминизм (FAD-Plus), оценка социально-демографических и поведенческих параметров с помощью опросных методов. Результаты. Обращение за эзотерическими услугами связано с рядом мировоззренческих убеждений и более распространено среди женщин и людей с высокой религиозностью. Вопреки выдвинутой гипотезе не обнаружено взаимосвязи обращения за эзотерическими услугами и толерантности к неопределенности. Основные выводы. Обращение за эзотерическими услугами тесно связано с мировоззренческими убеждениями. Вера в детерминизм (как фаталистический, так и научный) может являться фасилитатором обращения за подобными услугами, тогда как вера в непредсказуемость и свободу отрицательно связаны с использованием подобных услуг.